2020
DOI: 10.26714/lensa.8.1.2018.75-86
|View full text |Cite
|
Sign up to set email alerts
|

EFL Learners’ Responses on the Use of Performance-based Assessment

Abstract: Assessment is an ongoing process of evaluating learners' ability or skill after process of teaching and learning. In English class, assessment also plays an important role. According to the facts found, assessment mostly used in English class is traditional assessment. English class needs more alternative assessments to set the goals of learning English. Curriculum 2013, which is used in Indonesia right now, emphasizes the use of authentic assessment, and performance -based assessment is to be a subset of auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
0
11
1
Order By: Relevance
“…It might be because they have no idea about the topic assigned by the teacher. Their less knowledge lets them have more time searching for and exploring the ideas to write (Fraser, 2006;Prastikawati, 2018). Meanwhile, they are limited to the time of writing completion to get pressure in writing.…”
mentioning
confidence: 99%
“…It might be because they have no idea about the topic assigned by the teacher. Their less knowledge lets them have more time searching for and exploring the ideas to write (Fraser, 2006;Prastikawati, 2018). Meanwhile, they are limited to the time of writing completion to get pressure in writing.…”
mentioning
confidence: 99%
“…The result showed that the students were very enthusiastic to produce any performance for proving their competencies. Prastikawati (2018) found that the students had good responses to the learning activities done when the teacher used some performance-based assessments.…”
Section: Factors Building Students' Motivation Elementsmentioning
confidence: 98%
“…The purpose of assessment is to stimulate students in thinking, reacting to new situations, reviewing and revising work, evaluating their own and others' work, and communicating results verbally or visually [16]. In addition, it guides the students to be creative in learning activities which contains character values [17]. Teacher can determine assessment activities based on students interest.…”
Section: Blended Reading Assessmentmentioning
confidence: 99%